[REVIEW OF OPENING REMARKS] - SPARBER PG (Tufts Archival Research Center, 2007)
Memorandum from Peter Sparber to Samuel D. Chicolte Jr. with opening remarks for Chicolte's meeting on Operation Downunder. Provides three points to provide emphasis on; policy, majority rule and the remainder of the agenda.